Learning Innovation Through the Secret Round Game to Increase Students' Interest in Learning in SKI Lessons - Adenia Nur Saka Nirwana; Alya Putri Tiarno; Eka Aulia Putri; Irene Zahrotul Azka; Syarah Dwi Handayani (Mazidah: Journal Of Educational Research, 2026)
This study aims to address the low learning interest of students in Islamic Cultural History (SKI) at MI Ma'arif NU Banjaranyar by implementing PAI (Islamic Religious Education) educational games to enhance interest and cognitive understanding. The research utilized a qualitative approach involving 21 fourth-grade students as subjects. The results indicated that the educational games effectively made the SKI learning process active and expressive, significantly increasing students' motivation to compete and participate meaningfully. This research affirms that PAI educational games successfully resolved the issue of low learning interest and strengthened students' memory retention of the SKI material.